Liver cancer knowledge graph construction based on dynamic entity replacement and masking strategies RoBERTa-wwm-large-BiLSTM-CRF model with clinical Chinese EMRs - Zhang, Yichi; Hu, Xiaojun; Wang, Hailing; Liu, Ke; Gao, Yongbin; Jiang, Xiaoyan; Fan, Yingfang; Fang, Zhijun (Frontiers in Artificial Intelligence, 2025)
IntroductionLiver cancer is a leading cause of cancer-related mortality worldwide, necessitating advanced tools for diagnosis and management. Knowledge graphs (KGs) are crucial for advancing smart healthcare, but existing liver cancer-specific KGs are mostly derived from literature or public databases, lacking integration with real-world clinical data [e.g., Electronic Medical Records (EMRs)], creating a critical gap. Furthermore, there is currently no publicly available KGs specifically for liver cancer, creating a significant gap in structured clinical knowledge resources.MethodsThis study proposes a novel framework to construct the first Chinese liver cancer KG from Real-World Liver Cancer Electronic Medical Records (RLC-EMRs). A new named entity recognition (NER) model, DERM-RoBERTa-wwm-large-BiLSTM-CRF was developed that uses a Dynamic Entity Replacement and Masking (DERM) strategy to address data scarcity. Knowledge fusion was performed using the TF-IDF algorithm to standardize and integrate entities from clinical records, the professional medical website www.XYWY.com, and the CCMT-2019 terminology standard.ResultsThe final constructed liver cancer KG contained 46,364 entities and 296,655 semantic relationships. The proposed NER model achieved a state-of-the-art F1 score of 68.84% on the public CMeEE-v2 dataset. On the proprietary RLC-EMRs dataset, the model demonstrated high effectiveness with a precision of 93.23%, recall of 94.69%, and an F1 score of 93.96%. In addition, a KG-based retrieval system was successfully developed to query for complications, medications, and other related information.DiscussionThe findings demonstrated the effectiveness of the proposed framework in constructing a comprehensive and clinically relevant liver cancer KG. The novel DERM-based NER model significantly improved entity extraction from complex medical texts. By successfully integrating real-world clinical data, this study addresses a critical gap in existing liver cancer-specific KGs, which are mostly derived from literature or public databases and lack integration with real-world clinical information.